Radiographic study of endodontic treatment in adult population after period of time (Mustansiria Dental Journal, 2018)
The purpose of this study was to assess the treatment results following endodontictherapy of teeth filled with gutta-percha A total of 340 patients were used in this studyreferring to Al-Mustansirya University, 400 periapical radiographs of previouslyendodontic treated teeth were evaluated from patients were aged from 19-49 years oldselected amongst subjects referred to Al- Mustansirya dental collage, these patientshad been root filled for 12 months or greater.After samples selection, Radiographic examination was performed using theparallel technique with one periapical radiograph was taken for each tooth.Standardized exposure processing was used in order to obtain optimal diagnosticquality of the radiographs.Radiographs were assigned according to patient's sex and age, time elapsed sinceplacement of the root fillings, distance of root filling from radiographic apex whichmeasured directly from the radiographic categorized according to whether the rootfilling was less than 2 mm from the radiographic apex , or over filled teeth also painand presence or absence of radiolucency was recorded. In conclusion, teeth with rootcanal fillings material placed to within 2 mm of the radiographic apex wereassociated with higher success rates than fillings that were 2 mm or greater fromradiographic apex.